Pengaruh Investasi dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Provinsi Sumatera Utara Periode 2010-2022 - Sinaga, Epelima; Situmorang, Cheresentia; Siburian, Marshanda; Siagian, Irma; Sitohang, Mizael Demak; Hutasoit, Era Sulastri; Br Sitepu, Agnes Dea Lita; Banjarnahor, Yehezkiel Exaudi (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to examine the influence of investment and government spending on economic growth in North Sumatra Province during the 2010-2022 period. This research uses a quantitative approach by utilizing secondary data in the form of time series obtained from the Central Statistics Agency. Data analysis was carried out using descriptive methods and multiple linear regression analysis, which includes classic assumption testing and hypothesis testing using IBM SPSS Statistics 25 software. The research results show that both partially and simultaneously, government investment and spending have a significant influence on economic growth. In addition, the independent variables in this study were able to explain 96.1% of the variation in economic growth, while the remaining 3.9% was caused by other factors outside the research.